Q. 45.0( 1 Vote )

# Write the first five terms of each of the sequences. whose nth terms are an = an = Substituting n = 1, 2, 3, 4 and 5 we get

a1 = (2 x 1 - 3)/6 = -1/6

a2 = (2 x 2 - 3)/6 = (4 - 3)/6 = 1/6

a3 = (2 x 3 - 3)/6 = (6 - 3)/6 = 3/6 = ½

a4 = (2 x 4 - 3)/6 = (8 - 3)/6 = 5/6

a5 = (2 x 5 - 3)/6 = (10 - 3)/6 = 7/6

Therefore the first term is –1/6, 1/6, ½, 5/6 and 7/6.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Sequence & Series (Lecture 1)56 mins  Check Your progress Part 2| Interactive Quiz: Sequence & Series47 mins  Sequence & Series (Lecture 5)42 mins  Sequence & Series (Lecture 7)37 mins  Interactive quiz on inequalities involving AM and GM45 mins  Use of sigma in finding sum42 mins  Trigonometric Series45 mins  Sequence & Series (Lecture 6)42 mins  Sequence & Series (Lecture 8)35 mins  Check Your progress Part 3| Interactive Quiz: Sequence & Series46 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 